MANAJEMEN PRODUKSI PERTUNJUKAN MUSIK VIRTUAL BATAVIA CHAMBER ORCHESTRA - Komara, Detania Febryanti; Andriyanto, R.M. Aditya; Bagus Ketut Sudiasa, Ida (Jurnal Penelitian Musik, 2023)
Abstract: This study aims to identify and describe the production management process for virtual music performances in student orchestras held during a pandemic. The object of this research is the production management of the Batavia Chamber Orchestra musical performance “Virtual Colourchestra”. The research method used is a descriptive qualitative method. This research was carried out for 14 months, from December 2021 – January 2023. Data was obtained using literature studies, interviews, and documentation studies. The data analysis technique used is data reduction, data presentation, and data verification. In testing the validity of this research data using a triangulation technique carried out with a research expert, namely Airin Efferin. The results of this study indicate that the production management of virtual music performances performed by a student orchestra, namely the Batavia Chamber Orchestra, is following the principles and 4 management functions including planning, organizing, leading, and controlling. The Covid-19 pandemic has not only made music performances change in their presentation but also changes in terms of management.